A case of acute paraneoplastic neurological syndrome in BRAF mutant metastatic melanoma. Issue 4 (August 2016) - Lee, Shu F.; Atkinson, Victoria
Abstract : A 58-year-old man with indolent metastatic BRAF mutant melanoma presented with several days' history of progressive ataxia and dysdiadochokinesia. His PET/computed tomography restaging scan indicated two new fluorine-18-fluorodeoxyglucose-avid mesenteric lymph nodes. Meanwhile, his MRI brain and whole spine were within normal limits. A lumbar puncture indicated an elevated protein level with a normal cell count and negative paraneoplastic antibodies. Because of the lack of an alternative differential, the diagnosis of paraneoplastic syndrome was made. He was started on high-dose corticosteroids as well as dabrafenib and trametinib. Despite this, his neurological symptoms continued to progress. Consequently, he was trialed on a course of intravenous immunoglobulin, which stabilized his symptoms. He continued to improve over several weeks, with near-complete resolution of all his neurological symptoms, and showed a complete radiological response of his disease. To our knowledge, this is the first reported case of paraneoplastic neurological syndrome with mixed neurology associated with BRAF mutant cutaneous melanoma that responded to BRAF targeted therapy.